Caso de estudio: Contacto Corredores de Seguros S.A. - Mühlig Vega, Cynthia Margot (2023)
This work was carried out with the objective of developing a strategic plan for the company Contacto Corredores de Seguros S.A., organization dedicated to Risk Management and Insurance Management. To support the work, six chapters have been made in which the first three chapters will expose the introduction to the business, to the company and the strategic diagnosis. The macroenvironment and microenvironment will be studied so that the opportunities and threats that the company will have to take advantage of and face. In addition, their strengths and weaknesses will be indicated so that their can gain an advantage over their competitors and improve any weaknesses that have been found. In the last chapters, the formulation, implementation, and control of the company's proposed strategies are carried out. Also, the matrices will be developed that will help propose new strategies for the company. Finally, the strategic control map and the Balanced Scorecard will be implemented so that all the proposed objectives can be controlled through indicators and goals by the company itself.